2016
DOI: 10.1093/femspd/ftw019
|View full text |Cite
|
Sign up to set email alerts
|

Rifampicin-containing combinations are superior to combinations of vancomycin, linezolid and daptomycin againstStaphylococcus aureusbiofilm infectionin vivoandin vitro

Abstract: Susceptibility to antibiotics is dramatically reduced when bacteria form biofilms. In clinical settings this has a profound impact on treatment of implant-associated infections, as these are characterized by biofilm formation. Current routine susceptibility testing of microorganisms from infected implants does not reflect the actual susceptibility, and the optimal antibiotic strategy for treating implant-associated infections is not established. In this study of biofilm formation in implant-associated osteomye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 37 publications
5
29
0
Order By: Relevance
“…Finally, bacteria were suspended in 3% Tryptic Soy Broth (TSB) at a concentration of 1.5 × 10 6 colony forming units (CFU) per mL. Minimum inhibitory concentration (MIC) for daptomycin were 0.38 mg/L and 0.008 mg/L for rifampicin and the minimum biofilm eradication concentration (MBEC) value for daptomycin was 1024 mg/L as previously reported [33]. …”
Section: Methodsmentioning
confidence: 94%
“…Finally, bacteria were suspended in 3% Tryptic Soy Broth (TSB) at a concentration of 1.5 × 10 6 colony forming units (CFU) per mL. Minimum inhibitory concentration (MIC) for daptomycin were 0.38 mg/L and 0.008 mg/L for rifampicin and the minimum biofilm eradication concentration (MBEC) value for daptomycin was 1024 mg/L as previously reported [33]. …”
Section: Methodsmentioning
confidence: 94%
“…Regarding other biofilm settings, it has been found that combined treatment with clarithromycin plus daptomycin is useful to eradicate staphylococcal biofilms formed on orthopedic devices . Likewise, in another recent work, rifampicin‐containing combinations were superior to combinations of vancomycin, linezolid and daptomycin against S. aureus biofilm infection in vivo and in vitro . Other combinations such as ceftaroline plus daptomycin or vancomycin with fosfomycin were found to display potent activity against biofilm‐producing MRSA, thus providing a potential option for difficult‐to‐treat medical device infections.…”
Section: Antibiotic Treatment Strategies For Combating Biofilm Infectmentioning
confidence: 99%
“…Studies have shown that quinolones can effectively kill gramnegative bacteria in biofilms. Quinolones combined with RIF can significantly improve the success rate of osteomyelitis treatment and reduce the risk of bacterial resistance [18][19][20]. Clinically, Staphylococcus species comprises the major pathogenic bacteria that cause implant-or post-trauma-related bone infections.…”
mentioning
confidence: 99%